Installation of skillion roof / Nurul Hanis Hadi - Hadi, Nurul Hanis (Universiti Teknologi MARA, Perak, 2019)
A roof is the top covering of a building, including all materials and constructions necessary to support it on the walls of the building or on uprights. It provides protection against rain, snow, sunlight, extremes of temperature, and wind. A roof is part of the building envelope. This report was conducted for the building envelope at Kampung Kuala Wau, Maran, Pahang Darul Makmur. The building was 2-storey clinic which is located near to residential area. The objective of this report is to identify the type of roof used in the construction of clinic. Roof has many type and the type is depending on the what the building is and the weather also affected on the design of roof to make the building can function well. The next is how the roof of the clinic was built. It will focus on the method of roof construction. To build the roof, there is many step to follow. This report also highlights about advantages and disadvantages of type of roof used on site. A proper roof installation is very imp01tant to any building because it's can protect building and keeps the building dry.